NEO-GRAMSCIAN APPROACH ON EUROPEANIZATION - Mihail CARADAICĂ (Challenges of the Knowledge Society)
This paper belongs to the area of critical studies in European Integration and I will try to demonstrate that the concept of Europeanization is not able to capture the nature of social change which occurs in member states. Nowadays, this concept is largely used by scholars to describe all of the economic, political and social changes that are taking place in national domestic policy under the influence of the European Union, understood as a distinct polity. In other words, this approach of Europeanization is limited only to the European geographical space and, as a consequence, it cannot capture the wider context in which the European Union exists – globalization and the nature of world order. My aim is to analyse the concept of Europeanization through the neo-gramscian theoretical framework and to see if it can be overlapped with the process of European integration. I will do this by assuming a historical materialist view on the European integration process and international relations which will help me understand these changes through the Marxist perspective of structure and superstructure. Those concepts are mutually constructed in the neo-gramscian approach and they are represented by the agency of social forces and its superstructural dimension – the neoliberal ideology according to Baastian Van Apeldoorn, Andeas Bieler, Adam David Morton or Stephen Gill.